KONFLIK PADA KELUARGA DI KUANTAN SINGINGI (Studi Keluarga Yang Mempunyai Anak dan Tidak Mempunyai Anak Di Desa Munsalo) - Hukma Hasana; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The family is the smallest unit of a society. Nowadays, many families who do not have children are ignored by certain things that make the family can not have children or choose not to have children. Indeed, children in the family play a very important role in determining the continuity of a family relationship, where from several assumptions that children can minimize the occurrence of conflict in the family. Then what about a family couple who does not have children, whether in their family will be vulnerable to conflict and any conflicts that occur will make them vulnerable to end their relationship. Because there is no basis that will reinforce their conception to maintain each other's household. Therefore the authors want to see if true children can save a family relationship in an effort to minimize conflict in the family. This research was conducted by qualitative descriptive method and sampling purposive sampling. The sample consists of families who have children and families who do not have children. In this study, the author tries to tell and explain how the form of conflict that occurs in families who have children and do not have children. Furthermore, the researchers also revealed the factors that caused the conflict in the family in the Village Munsalo Kuantan Singingi.Key Words : Conflict, family childhood, and no-childhood